2014
DOI: 10.3762/bjoc.10.291
|View full text |Cite|
|
Sign up to set email alerts
|

Inherently chiral calix[4]arenes via oxazoline directed ortholithiation: synthesis and probe of chiral space

Abstract: SummaryThe diastereoselective oxazoline-directed lithiation of calix[4]arenes is reported with diastereoselective ratios of greater than 100:1 in some instances. Notably, it has been found that the opposite diastereomer can be accessed via this approach merely through the choice of an alkyllithium reagent. The inherently chiral oxazoline calix[4]arenes have also been preliminarily examined as ligands in the palladium-catalyzed Tsuji–Trost allylation reaction, returning results comparable to their planar chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We, like some others, [6] have focused our approach towards the meta-substitution pattern. [5] We have also reported that a [4]arene. In this regard, we have already demonstrated that chiral oxazolines can be used to stereoselectively direct ortholithiation of calix [4]arenes and give inherently chiral calixarenes in high diastereomeric excess.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…We, like some others, [6] have focused our approach towards the meta-substitution pattern. [5] We have also reported that a [4]arene. In this regard, we have already demonstrated that chiral oxazolines can be used to stereoselectively direct ortholithiation of calix [4]arenes and give inherently chiral calixarenes in high diastereomeric excess.…”
Section: Introductionmentioning
confidence: 75%
“…Interestingly, the 1 H NMR spectrum of calix [4]arene substituted with the chiral sulfoxide 2 revealed the incorporated tert-butyl group to resonate at δ = 0.61 ppm, which was significantly upfield shifted compared to δ = 1.16 ppm for the analogous p-methoxyaryl sulfoxide. [5] We then examined diethyl ether as a solvent, but this resulted in no conversion after lithiation for eight hours at -78°C. This result looked promising regarding the ability of the sulfoxide to asymmetrically direct ortholithiation, since a preferred conformation was expected to lead to a high degree of diastereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations